Hierarchia kultury na tle nierówności ekonomicznych i kapitału społecznego - Domański, Henryk (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
Cultural inequality is one of the constitutive factors of the class structure. This analysis aims to determine the extent to which cultural participation reflects class inequalities in comparison with two other dimensions of the class structure, i.e. economic inequalities and social capital. Cultural participation is measured in terms of musical tastes. Drawing on data from a 2019 research conducted on a representative sample in Poland, I attempt to assess the role of this variable in shaping class structure. The findings show that class distances are better reflected in economic inequalities (family income) than in musical tastes – with a minor role of social capital – which confirms the hypothesis. The same pattern is reflected in the effect of father’s class on family income and cultural capital, which indicates intergenerational transmission of these factors.